Berolahraga Aman Di Masa Pandemi COVID-19 - Muhammad Perdana Airlangga (PROCEEDING UMSURABAYA, 2020)
AbstractPhysical activity has proven to be beneficial in improving the clinical conditions that are mostfrequently associated with severe COVID-19. Physical activity contributes to the reduction ofoverall cardiovascular risks, lowering both systolic and diastolic blood pressure andremodeling left ventricular hypertrophy. The immune system is highly responsive to physicalactivity, with the extent of the response related to both duration and intensity of exercise.Moderate-intensity exercise training is associated with a reduced incidence. Social isolation/distancing (‘‘stay home’’) can increase sedentary behavior and decrease the level of physicalactivity, which has already been linked to poor survival rates The current review summarizesharmful effects of limited physical activity on mental and physical health due to socialdistancing and quarantine and highlights the effects of simple physical activity regimescounteracting these detrimental effects.Keyword : COVID-19, Physical activity, Home exercise program